Вишенка-2 – новый чернолесско-жаботинский памятник в Среднем Побужье - Бойко, Ю.Н. (My University, 2004)
Yu. Boyko. Visbenka-2 — New Cbemolesye-Zbabotin Antique in the Middle Bug Region The article contains the detailed analysis of results of excavation of the single VIII century B.C. hole in the excavated settlement in the Eastern Podolye. It shows cultural connections between native inhabitants of the Bug — Dniester territory and migrants to the Vorskla region. The conclusion about neuroi origin of this kind of people is drawn in it.